Survey integrato per la ricostruzione del porto di Haiti - Faccioli, Andrea (GEOmedia, 2019)
On 12 January 2010, a terrible earthquake struck the Caribbean state of Haiti. In addition to the numerous victims and the huge damages, the earthquake seriously damaged the port of the capital, Port-au-Prince. In particular, it completely destroyed the 450-meter North Pier, dedicated to the container traffic, making it impossible to disembark humanitarian aid and goods. Given the strategic importance of the infrastructure, the Ministry of Economy and Finance of Haiti has financed the design and reconstruction of Port-au-Prince, starting from the North pier. After the earthquake, the first step was a series of bathymetric, hydrogeological, topographical and aerial surveys realized by an Italian company.